Method for selecting compaction density of pole piece
By observing the number of particles of particles at the section of the polar section, analyzing the relationship with the density of compact, determining the best compact density of the polar film, solving the problem of complex and time -consuming problems in the existing technologies to test the best pressure density density. It has achieved simple and fast material assessment and battery performance improvement.
Patent Information
- Application Number
- CN202310928749.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-01-28
AI Technical Summary
The method of testing the optimal compaction density of the pole sheet in the prior art is complex and time-consuming, resulting in long material evaluation time and high cost.
By preparing pole films with different density, observe the section and count the number of particles of particle crushing, analyze the change in the relationship between the density and the number of particles crushing, and determine the best compact density of the pole.
This method is simple and fast, which greatly reduces the time selection of polar pressure density, improves work efficiency, and effectively improves the energy density and electrochemical performance of lithium -ion batteries.
Smart Images

Figure CN119375094A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a method for selecting the compaction density of a pole piece. Background Art
[0002] With the popularity of new energy vehicles and consumer electronics, the demand for lithium-ion batteries is increasing, especially high-performance lithium-ion batteries with high specific energy. Compacted density is an important indicator for improving energy density and electrochemical performance of lithium-ion batteries. Compacting the pole piece can improve the contact between particles in the pole piece coating, as well as the contact between the pole piece coating and the current collector, and reduce the contact internal resistance. At the same time, the higher the compacted density, the more active substances the lithium-ion battery pole piece will contain per unit volume, so the energy density of the lithium-ion battery can be effectively improved. However, if the compacted density is too high, the porosity will be lost, the tortuosity of the pores will increase, and the diffusion, embedding and de-embedding of lithium ions will be restricted. The lithium-ion diffusion resistance will increase, and the battery rate performance will decrease. At the same time, during the production process, the pole piece is very easy to break, causing irreparable losses. Therefore, obtaining the optimal compacted density of the pole piece is crucial to the manufacture and design of the battery.
[0003] At present, the best compaction density of the electrode is usually tested by assembling the electrodes with different compaction densities into batteries, and then testing the electrical properties of the batteries to obtain the best compaction density. This testing method is complicated, time-consuming and costly. Therefore, it is urgent to develop a simple and fast method for selecting the compaction density of the electrode. Summary of the invention
[0004] In view of the above shortcomings of the prior art, the present invention provides a method for selecting the compaction density of a pole piece, so as to improve the problem that the current method for selecting the compaction density of a pole piece is complicated and takes a long time to test.
[0005] To achieve the above-mentioned purpose and other related purposes, the present invention provides a method for selecting the compaction density of an electrode, the method comprising: a preparation step of preparing a plurality of electrode pieces with different compaction densities; an observation step of observing the cross-sections of the plurality of electrode pieces respectively and counting the number of particle breakages of each of the electrode pieces at the cross-section; an analysis step of analyzing the changing relationship between the compaction density of the plurality of electrode pieces and the number of particle breakages, if the number of particle breakages deviates positively with the linear increase of the compaction density, then the compaction density before the positive deviation is determined as the compaction density of the electrode piece.
[0006] In one example of the present invention, the preparation steps include: preparing electrode slurry and coating the electrode slurry on a current collector; baking and drying the current collector coated with the electrode slurry; cutting the dried current collector coated with the electrode slurry into a plurality of primary pole sheets; and rolling the plurality of primary pole sheets at different pressures to obtain a plurality of pole sheets with different compaction densities.
[0007] In one example of the present invention, the compaction density is obtained by taking a double-sided coated wafer per unit area of the target electrode and calculating it using the following formula: ρ = (m-m0) / (A*(h-h0)), wherein ρ is the compaction density, m is the mass of the wafer per unit area, m0 is the mass of the current collector part of the wafer, h is the thickness of the wafer, h0 is the thickness of the current collector part of the wafer, and A is the area of the wafer.
[0008] In an example of the present invention, the coating composition and coating surface density of the plurality of pole pieces are the same.
[0009] In an example of the present invention, the compaction density of the plurality of pole pieces increases in the same compaction step.
[0010] In one example of the present invention, the compaction step length is less than or equal to 0.05 g / cm 3 .
[0011] In one example of the present invention, the observation step includes: ion grinding and sectioning the plurality of pole pieces with different compaction densities to obtain cross sections of the plurality of pole pieces; observing the cross sections of the plurality of pole pieces at the same magnification, and counting the number of broken particles of each pole piece at the cross section.
[0012] In an example of the present invention, the analysis step includes: drawing a compaction density-particle crushing number relationship curve with compaction density as the horizontal coordinate and the particle crushing number as the vertical coordinate; analyzing the changing trend of the particle crushing number with the increase of the compaction density based on the compaction density-particle crushing number relationship curve; if the particle crushing number deviates positively with the linear increase of the compaction density, the compaction density before the positive deviation is determined as the compaction density of the pole piece.
[0013] In an example of the present invention, the electrode sheet is a positive electrode sheet, and the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on at least one side of the positive electrode current collector.
[0014] In one example of the present invention, the positive electrode active material layer includes a positive electrode material, a conductive agent and a binder, and the positive electrode material is selected from a ternary material or a lithium-containing phosphate.
[0015] The method for selecting the compaction density of the pole piece of the present invention obtains the optimal compaction density of the pole piece by observing the morphology of the pole piece at different compaction densities, counting the number of particle crushing at different compaction densities, and according to the changing relationship between the compaction density and the number of particle crushing. The method is simple and fast, and can greatly reduce the material evaluation time and improve work efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 A flow chart of a method for selecting a pole piece compaction density provided in one embodiment of the present invention;
[0018] Figure 2 A flow chart of the preparation steps provided in one embodiment of the present invention;
[0019] Figure 3 A flowchart of an observation step provided in one embodiment of the present invention;
[0020] Figure 4 A flowchart of an analysis step provided in one embodiment of the present invention;
[0021] Figure 5 The positive electrode sheet (LiNi 0.67 Co 0.05 Mn 0.28 O2) Scanning electron microscope (SEM) images of the cross section at different compaction densities, where (a) is the compaction density of 3.45g / cm 3 SEM image of the positive electrode section. Figure (b) is a compaction density of 3.50g / cm 3 SEM image of the positive electrode section. Figure (c) shows a compaction density of 3.55 g / cm 3 SEM image of the positive electrode section. Figure (d) shows a compaction density of 3.60 g / cm 3 SEM image of the cross-section of the positive electrode.
[0022] Figure 6 The positive electrode sheet (LiNi 0.67 Co 0.05 Mn 0.28 O2) Relationship between the number of particle crushing and compaction density;
[0023] Figure 7 The positive electrode sheet (LiNi 0.65 Co 0.07 Mn 0.28 O2) SEM images of the cross section at different compaction densities, where (a) is the compaction density of 3.45g / cm 3SEM image of the positive electrode section. Figure (b) is a compaction density of 3.50g / cm 3 SEM image of the positive electrode section. Figure (c) shows a compaction density of 3.55 g / cm 3 SEM image of the positive electrode section. Figure (d) shows a compaction density of 3.60 g / cm 3 SEM image of the cross section of the positive electrode;
[0024] Figure 8 The positive electrode sheet (LiNi 0.65 Co 0.07 Mn 0.28 The relationship between the number of crushed particles and the compacted density in O2). DETAILED DESCRIPTION
[0025] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.
[0026] For simplicity, only some numerical ranges are explicitly disclosed herein, and each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unspecified range.
[0027] In the manufacture of lithium-ion batteries, the compaction density has a great influence on battery performance. Experiments have shown that the compaction density is closely related to the sheet specific capacity, efficiency, internal resistance and battery cycle performance. Generally speaking, the higher the compaction density, the greater the battery capacity. However, if the compaction density is too high, the porosity is lost, the tortuosity of the pores increases, and the diffusion, embedding and de-embedding of lithium ions are restricted. The lithium ion diffusion resistance increases and the battery rate performance decreases. Therefore, finding the optimal compaction density of the pole piece is crucial for battery design.
[0028] The present invention provides a method for selecting the compaction density of a pole piece. By observing the microscopic morphology of the pole piece cross section at different compaction densities, the number of particle breakages can be directly and quantitatively counted. Particle breakage is directly related to the electrical performance of the battery. The more particles are broken, the more fresh interfaces are exposed, and the long-term stability of the battery will be poor. Based on this, by analyzing the changing trend of the number of particle breakages as the compaction density increases, the optimal compaction density of the pole piece can be obtained. The method is simple and fast, and can greatly reduce the time for selecting the compaction density of the pole piece.
[0029] See also Figure 1 The method for selecting the compaction density of the pole piece provided by the present invention comprises:
[0030] S1, preparation step, preparing a plurality of pole pieces with different compaction densities;
[0031] S2, an observation step, observing the cross sections of multiple pole pieces respectively, and counting the number of broken particles at the cross sections of each pole piece;
[0032] S3. Analysis step: analyzing the changing relationship between the compaction density of the pole piece and the number of particle crushes. If the number of particle crushes deviates positively with the linear increase of the compaction density, the compaction density before the positive deviation is determined as the compaction density of the pole piece.
[0033] The pole piece in step S1 includes a current collector and an active material layer coated on at least one side of the current collector, the composition and coating surface density of the active material layers of the plurality of pole pieces are kept the same, and the coated pole pieces are rolled at different pressures to obtain a plurality of pole pieces with different compaction densities. It should be noted that the pole piece of the present invention can be a positive pole piece or a negative pole piece.
[0034] See also Figure 2 In step S1, a plurality of pole pieces with different compaction densities are prepared, including steps S11 to S14, which are specifically described as follows:
[0035] S11, preparing electrode slurry, and coating the electrode slurry on the current collector.
[0036] In this step, the composition of the electrode slurry is selected according to the type of electrode sheet. If the electrode sheet to be prepared is a positive electrode sheet, the electrode slurry is a positive electrode slurry. If the electrode sheet to be prepared is a negative electrode sheet, the electrode slurry is a negative electrode slurry.
[0037] The positive electrode slurry includes a positive electrode material, a binder, a conductive agent and a solvent. The positive electrode material is selected from ternary materials, lithium-containing phosphates and other materials conventionally used in the positive electrode of the battery in the art, wherein the ternary materials include but are not limited to lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide; lithium-containing phosphates include but are not limited to lithium iron manganese phosphate, lithium iron phosphate, lithium manganese phosphate, and the like. Conductive agents and binders can be selected from conventional material types in the art, for example, the conductive agent is selected from one or more of carbon black, acetylene black, graphene, carbon nanotubes, and carbon nanofibers; the binder is selected from polyvinylidene fluoride or polytetrafluoroethylene. The solvent is selected from N-methylpyrrolidone, referred to as NMP. The positive electrode material, the conductive agent and the binder are dispersed in NMP in a certain proportion to form a uniform positive electrode slurry. The ratio between the components in the positive electrode slurry can be set with reference to the conventional ratio, and is not limited here.
[0038] The negative electrode slurry includes a negative electrode material, a binder, a conductive agent, a thickener and a solvent. The negative electrode material is selected from one or more of artificial graphite, natural graphite, soft carbon, hard carbon, pure silicon, silicon oxide compounds, and silicon carbon compounds. The conductive agent is selected from one of carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc., or a combination of two or more mixed in any proportion. The binder is selected from any one of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), or a combination of several mixed in any proportion; the thickener is selected from sodium carboxymethyl cellulose (CMC-Na) or lithium carboxymethyl cellulose (CMC-Li). The negative electrode material, negative electrode binder, thickener and negative electrode conductive agent are dispersed in deionized water in a certain proportion to form a uniform negative electrode slurry. Among them, the ratio between the components in the negative electrode slurry can be set with reference to the conventional ratio, and is not limited here.
[0039] The current collector in this step is a material with good conductivity and mechanical strength. For example, the current collector of the positive electrode sheet can be aluminum foil, and the current collector of the negative electrode sheet can be copper foil. When coating the electrode slurry, it is necessary to ensure that the coating surface density of multiple electrode sheets remains consistent.
[0040] Step S12: baking and drying the current collector coated with the electrode slurry.
[0041] The purpose of this step is to fix the electrode slurry on the current collector. The baking method and temperature can be set according to the conventional methods in the art, for example, drying in a vacuum oven at 80° C. for 12 hours.
[0042] Step S13, cutting the dried current collector coated with the electrode slurry into a plurality of primary electrode sheets.
[0043] This step is to cut the current collector coated with the electrode slurry into multiple pieces, so as to facilitate the subsequent rolling of multiple primary pole pieces with different pressures to obtain pole pieces with different compaction densities.
[0044] In other embodiments, multiple current collectors may be directly coated with the same electrode slurry, and the coating surface density of each current collector is kept consistent.
[0045] Step S14, rolling the plurality of primary pole pieces at different pressures to obtain a plurality of pole pieces with different compaction densities.
[0046] Select different pressure values within a certain pressure range to vertically press multiple primary pole pieces, and measure the total thickness of the pole pieces after pressing and the thickness of the current collector in the pole pieces. Calculate the compaction density ρ of each pole piece according to the following formula based on the measured data:
[0047] ρ=(m-m0) / (A*(h-h0)),
[0048] Wherein, m is the mass of the wafer per unit area, m0 is the mass of the current collector part in the wafer, h is the thickness of the wafer, h0 is the thickness of the current collector part in the wafer, and A is the area of the wafer.
[0049] In some embodiments, the compaction densities of the plurality of pole pieces are increased in the same compaction step, that is, the intervals between adjacent compaction densities are the same. For example, the compaction densities of the plurality of pole pieces are 3.45 g / cm 3 、3.50g / cm 3 、3.55g / cm 3 、3.60g / cm 3 , ……3.45+0.05(n-1)g / cm 3 , where n is a positive integer. Preferably, the compaction step length is less than or equal to 0.05 g / cm 3 , for example, the compaction step length is 0.01g / cm 3 , 0.03g / cm 3 , 0.05g / cm 3 The smaller the compaction step size, the closer the compaction density is to the optimal compaction density. However, if the compaction step size is too small, the microscopic morphology of the cross section at adjacent compaction densities is not much different, and the test time is too long.
[0050] See also Figure 1 and Figure 3 Step S2, respectively observing the microscopic morphology of multiple pole piece cross sections, and counting the number of broken particles at each pole piece cross section, including steps S21 to S22, which are specifically described as follows:
[0051] S21, ion grinding and sectioning the plurality of pole pieces with different compaction densities respectively to obtain cross sections of the plurality of pole pieces.
[0052] This step uses argon ion beam cutting technology to cut the pole piece, which can avoid the problem of uneven cutting surface caused by mechanical cutting. Argon ion beam cutting technology is considered to be the best choice for obtaining stress-free and pollution-free flat cross-sections with high efficiency and low cost.
[0053] S22. Observe the cross sections of multiple pole pieces at the same magnification, and count the number of broken particles at the cross section of each pole piece.
[0054] In this step, a scanning electron microscope is used to observe the breakage of particles at the cross section of each pole piece under the same magnification. There is no limit on the magnification here, as long as the morphology of the particles at the cross section can be clearly observed, but it is necessary to ensure that the magnification of each pole piece remains consistent. For example, a magnification of 5000 times is used for observation, and the number of broken particles at the cross section of each pole piece is counted.
[0055] See also Figure 1 and Figure 4 Step S3, an analysis step, that is, analyzing the relationship between the compaction density and the number of particle crushing according to the number of particle crushing at different compaction densities counted in the observation step, specifically includes steps S31 to S32:
[0056] Step S31, plotting a relationship curve between compaction density and particle crushing number, with compaction density as the horizontal coordinate and particle crushing number as the vertical coordinate.
[0057] Among them, the compaction step length of the horizontal axis compaction density is the same, and then according to the number of particle crushing corresponding to different compaction densities counted in step S2, the coordinate points corresponding to each pole piece are drawn in the coordinate system, and then the coordinate points are connected in sequence with a curve to obtain a compaction density-particle crushing number relationship curve.
[0058] Step S32: analyzing the changing trend of the number of crushed particles as the compaction density increases based on the compaction density-particle crushing number relationship curve.
[0059] If the number of broken particles increases linearly with the increase of compaction density, it means that the optimal compaction density of the electrode has not appeared and the compaction density needs to be further increased; if the number of broken particles deviates positively with the linear increase of compaction density (that is, the number of broken particles is greater than the number of broken particles that increases linearly with the compaction density), it means that the number of broken particles has a sudden change under this compaction density, and the more broken particles are, the more fresh interfaces are exposed, and the long-term stability of the battery will deteriorate. At this time, we determine the compaction density before the positive deviation as the optimal compaction density of the electrode.
[0060] In order to further understand the technical scheme of the present invention, the present invention is further described in detail below through specific embodiments. The following embodiments are only simple examples of the present invention and should not be construed as restrictive. Within the scope consistent with the gist of the present invention, appropriate modifications can be made, which all fall within the technical scope of the present invention.
[0061] Example 1
[0062] (1) Preparation step: the positive electrode material LiNi 0.67 Co 0.05 Mn 0.28 O2 (denoted as sample 1) was mixed with conductive agent conductive carbon black (Super P) and binder polyvinylidene fluoride (PVDF) in a weight ratio of 97:1.5:1.5, N-methylpyrrolidone (NMP) was added, and the mixture was stirred under the action of a vacuum mixer until the system was uniform to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on an aluminum foil; the aluminum foil coated with the positive electrode slurry was dried at room temperature, and then transferred to a vacuum drying oven at 80°C for drying for 12 hours; the dried aluminum foil was then cut into four primary electrode sheets, and the four primary electrode sheets were rolled at different pressures to obtain compaction densities of 3.45 g / cm 3 、3.50g / cm 3 、3.55g / cm 3 、3.60g / cm 3 The four positive electrodes.
[0063] (2) Observation step: the four positive electrode sheets are cut by argon ion beam cutting technology to obtain the cross section of each electrode sheet, and then the cross section of each electrode sheet is observed by scanning electron microscope at a magnification of 5000 times (see Figure 5 ), and count the number of broken particles at each section.
[0064] (3) Analysis steps: plot the relationship between the compaction density and the number of broken particles of sample 1, with the compaction density as the horizontal axis and the number of broken particles as the vertical axis. Figure 6 .
[0065] from Figure 5 It can be clearly seen that when the compaction density is 3.45g / cm 3 (Figure (a)) and 3.50g / cm 3 (Figure (b)), no obvious broken particles were found in the pole piece of sample 1, and when the compaction density was 3.55g / cm 3 (Figure (c)) and 3.60g / cm 3 (Figure (d)), obvious particle fragmentation occurred. Figure 6 It is not difficult to find that the compacted density is 3.55g / cm 3When the particle size of the sample 1 at the pole piece section changes suddenly, the number of broken particles increases much more than the compaction density increases from 3.45 to 3.50 g / cm 3 The increase in the number of particle breakages) shows that the optimal compaction density of the pole piece of sample 1 is 3.50 g / cm 3 .
[0066] Example 2
[0067] (1) Preparation steps, using positive electrode material LiNi 0.65 Co 0.07 Mn 0.28 O2 (denoted as sample 2) was mixed with conductive agent conductive carbon black (Super P) and binder polyvinylidene fluoride (PVDF) in a weight ratio of 97:1.5:1.5, and N-methylpyrrolidone (NMP) was added. The mixture was stirred under the action of a vacuum mixer until the system was uniform to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum foil. The aluminum foil coated with the positive electrode slurry was dried at room temperature and then transferred to a vacuum drying oven at 80°C for drying for 12 hours. The dried aluminum foil was then cut into four primary electrode sheets, and the four primary electrode sheets were rolled at different pressures to obtain compaction densities of 3.45 g / cm 3 、3.50g / cm 3 、3.55g / cm 3 、3.60g / cm 3 The four positive electrodes.
[0068] (2) Observation step: the four positive electrode sheets are cut by argon ion beam cutting technology to obtain the cross section of each electrode sheet, and then the cross section of each electrode sheet is observed by scanning electron microscope at a magnification of 5000 times (see Figure 7 ), and count the number of broken particles at each section.
[0069] (3) Analysis steps: plot the relationship between the compaction density and the number of broken particles of sample 2 with the compaction density as the horizontal axis and the number of broken particles as the vertical axis. Figure 8 .
[0070] from Figure 7 It can be clearly seen that when the compaction density is 3.45g / cm 3 (Figure (a)) and 3.50g / cm 3 (Figure (b)), no obvious broken particles were found in the pole piece of sample 2, and when the compaction density was 3.55g / cm 3 (Figure (c)) and 3.60g / cm 3 (Figure (d)), obvious particle fragmentation occurred. Figure 8It is not difficult to find that the compacted density is 3.55g / cm 3 When the number of broken particles at the cross section of sample 2 increased, there was a sudden change (i.e., the increase in the number of broken particles was much greater than the increase in the compaction density from 3.45 to 3.50 g / cm 3 The increase in the number of particle crushing) shows that the optimal compaction density of the pole piece of sample 2 is 3.50g / cm 3 .
[0071] Example 3
[0072] The same method as in Example 1 was used to 0.8 Co 0.1 Mn 0.1 The compaction density of the O2 positive electrode was selected, and the results showed that its optimal compaction density was 3.45g / cm 3 .
[0073] Example 4
[0074] The same method as in Example 1 was used to 0.7 Co 0.1 Mn 0.2 The compaction density of the O2 positive electrode was selected, and the results showed that its optimal compaction density was 3.45g / cm 3 .
[0075] Example 5
[0076] The same method as in Example 1 was used to 0.6 Co 0.1 Mn 0.3 The compaction density of the O2 positive electrode was selected, and the results showed that the optimal compaction density was 3.5g / cm 3 .
[0077] Example 6
[0078] The same method as in Example 1 was used to 0.55 Co 0.1 Mn 0.35 The compaction density of the O2 positive electrode was selected, and the results showed that its optimal compaction density was 3.4g / cm 3 .
[0079] Example 7
[0080] The same method as in Example 1 was used to 0.33 Co 0.33 Mn 0.34 The compaction density of the O2 positive electrode was selected, and the results showed that its optimal compaction density was 3.3g / cm 3 .
[0081] The present invention observes the morphology of the pole piece at different compaction densities, counts the number of particle crushes at different compaction densities, and obtains the optimal compaction density of the pole piece based on the changing relationship between the compaction density and the number of particle crushes. The method is simple and fast, and can greatly reduce the material evaluation time and improve work efficiency. Therefore, the present invention effectively overcomes some practical problems in the prior art and has high utilization value and use significance.
[0082] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for selecting the compaction density of a pole piece, characterized in that: include: A preparation step, preparing a plurality of pole pieces with different compaction densities; an observation step of observing the cross sections of the plurality of pole pieces respectively and counting the number of broken particles at the cross sections of the pole pieces; An analysis step is to analyze the changing relationship between the compaction density of the plurality of pole pieces and the number of particle crushes. If the number of particle crushes deviates positively with the linear increase of the compaction density, the compaction density before the positive deviation is determined as the compaction density of the pole piece.
2. The method for selecting the pole piece compaction density according to claim 1, characterized in that: The preparation steps include: Preparing an electrode slurry and coating the electrode slurry on a current collector; baking and drying the current collector coated with the electrode slurry; Cutting the dried current collector coated with the electrode slurry into a plurality of primary electrode sheets; The plurality of primary pole pieces are rolled at different pressures to obtain a plurality of pole pieces with different compaction densities.
3. The method for selecting the pole piece compaction density according to claim 1, characterized in that: The compaction density is obtained by taking a double-sided coated disc per unit area of the target pole piece and calculating it using the following calculation formula: ρ=(m-m0) / (A*(h-h0)), Wherein, ρ is the compaction density, m is the mass of the disc per unit area, m0 is the mass of the current collector part in the disc, h is the thickness of the disc, h0 is the thickness of the current collector part in the disc, and A is the area of the disc.
4. The method for selecting the pole piece compaction density according to claim 1, characterized in that: The coating composition and coating surface density of the plurality of pole pieces are the same.
5. The method for selecting the pole piece compaction density according to claim 1, characterized in that: The compaction density of the plurality of pole pieces increases in a same compaction step.
6. The method for selecting the pole piece compaction density according to claim 5, characterized in that: The compaction step length is less than or equal to 0.05 g / cm 3 .
7. The method for selecting the pole piece compaction density according to claim 1, characterized in that: The observation step comprises: ion grinding and sectioning the plurality of pole pieces with different compaction densities respectively to obtain cross sections of the plurality of pole pieces; The cross sections of the plurality of pole pieces are observed at the same magnification, and the number of broken particles of each pole piece at the cross section is counted.
8. The method for selecting the pole piece compaction density according to claim 1, characterized in that: The analysis step comprises: The relationship curve between compaction density and particle crushing number is drawn with compaction density as the horizontal axis and particle crushing number as the vertical axis; Based on the compaction density-particle breakage number relationship curve, the changing trend of the particle breakage number with the increase of the compaction density is analyzed; if the particle breakage number deviates positively with the linear increase of the compaction density, the compaction density before the positive deviation is determined as the compaction density of the pole piece.
9. The method for selecting the pole piece compaction density according to claim 1, characterized in that: The electrode sheet is a positive electrode sheet, and the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer coated on at least one side of the positive electrode current collector.
10. The method for selecting the pole piece compaction density according to claim 9, characterized in that: The positive electrode active material layer comprises a positive electrode material, a conductive agent and a binder, and the positive electrode material is selected from a ternary material or a lithium-containing phosphate.